Physics in Ultra-Strong Magnetic Fields. Issue Volume 16:Issue S363(2020) (June 2020) - Harding, Alice K.
Abstract: Several populations of neutron stars have surface magnetic fields above the critical strength of 4.4 × 10 13 G where the electron cyclotron energy equals its rest mass. These include high-field rotation-powered pulsars, X-ray dim isolated neutron stars (XDIN), and magnetars. In such ultra-strong fields, quantum effects in physical processes as well as additional exotic Quantum Electrodynamic processes only occurring at these high field strengths have a significant influence on the emitted radiation. Although very strong magnetic fields play a critical role both inside and outside of neutron stars, I will review primarily processes that operate in the neutron star magnetospheres and how they influence the observed radiation.